THE ROLE OF SOCIAL SUPPORT ON TREATMENT ADHERENCE IN TB PATIENTS: A SYSTEMATIC REVIEW - Ardila Lailatul Barik; Retno Indarwati; Sulistiawati Sulistiawati (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2020)
Background: Adherence to treatment regimens in TB patients was carried out by using a pharmacological and non-pharmacological approach or paying attention to the social aspects of the patient.Objective: This review is to analyze and identify the literature related to the social support approach to treatment adherence in TB patients.Design: The systematic design of this review is to find and review journal articles from the database using Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA).Data Sources: This systematic review is based on literature studies from various journal data bases in the last 5 years, including Scopus, ScienceDirect, ProQuest and Google Scholar by conducting a comprehensive review. The keywords in this Systematic review are adjusted to the Medical Subject Heading (MeSH) and use a combination of Boolean operators (AND and OR), namely